(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A person is identified by gender as male or female in society and correspondingly carries on their social roles and responsibilities. For centuries, society has assigned different roles making the biological distinction of gender. This difference has developed a concept that men and women have separate roles to play and thus refrain from equality. Correspondingly, this categorization is a setback for those between the two male or female gender. Transgender people or hijras or eunuchs, known by many names, have been an intrinsic part of society and have recorded their presence in the world’s history. With time, transgender peoples’ positions have differed and, eventually, their importance in society. From time to time, authors in literary sphere have unveiled the subaltern status of the transgender community and depicted the pathetic conditions and discrimination they have faced in every sphere of life. In her recent work, The Ministry of Utmost Happiness, Arundhati Roy has portrayed the immense potential of a transgender person. She includes in the second novel, which is an active member of the society and, as a mouthpiece, depicts the lives of the hijra community and their position in the social sphere. For ages, the community has been subjected to mockery and looked down upon for their distinctive identity and presented as ‘other’. This paper explores transgender people’s prominence in different periods and their inclusion in the literary sphere and society.